Does the fossil fuel divestment movement impact new oil and gas fundraising? - Cojoianu, T; Ascui, F; Clark, G; Hoepner, A; Wojcik, D (Oxford University Press, 2020)
This paper explores whether increasing fossil fuel divestment commitments are related to the reduction of capital flows into the oil and gas sector, based on an analysis of syndicated lending, equity and bond underwriting across 33 countries from 2000 to 2015. We find that increasing oil & gas divestment pledges in a country are associated with lower capital flows to domestic oil and gas companies. This effect is enhanced in more stringent environmental policy regimes and diminished in countries which heavily subsidise fossil fuels. However, the divestment movement may have an unintended effect, insofar as domestic banks situated in countries with high divestment commitments and stringent environmental policies provide more finance to oil and gas companies abroad. We explain these findings through the lens of institutional theory, and show how both regulatory and socially normative elements of institutions shape this dynamic.